PENAMBATAN MOLEKUL SENYAWA VOLATIL EKSTRAK DIKLOROMETANA SAMBILOTO TERHADAP JALUR PENSINYAL EPIDERMAL GROWTH FACTOR RECEPTOR: Penambatan Molekul Senyawa Volatil Ekstrak Diklorometana Sambiloto Terhadap Onkoprotein Human Epidermal Growth Factor Receptor - Muhammad Faisal; Nurlaili Nurlaili; Potchanapond Graidist; Varomyalin Tipmanee (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2022)
EGFR oncoprotein has been commonly studied in combating cell cancer development. However, until this moment the EGFR inhibitors were reported to cause other health issues. Plant extracts are trusted as the potential inhibitor of EGFR expression level without affect our health. We previously observed seventeen volatile compounds in the dichloromethane extract of Andrographis paniculata. Our objective was to analyze the interaction of volatile compounds from the dichloromethane extract of Andrographis paniculata on human EGFR pathway. In silico technique with ligand-receptor molecular docking was used in this study. The structure of volatile compounds was set as the ligands. EGFR, PIK3CA, KRAS-GTP, BRAF V600E, and AKT protein structures were assigned as the receptors. PyRx and Biovia Discovery Studio were used in this docking study. Drug-likeness and lead-likeness properties were appraised by SwissADME and Pre-ADME/Tox web tools. Beta-amyrin and stigmasterol showed the highest binding affinity to EGFR oncoproteins. PIK3CA, AKT, and KRAS-GTP, BRAF V600E was bound to beta-amyrin and stigmasterol, respectively. Those compounds structurally showed drug-likeness and non-mutagenic. Briefly, beta-amyrin and stigmasterol will be potentially used as the inhibitors of selected oncoproteins. In vitro technique and animal model are suggested to be performed to validate the mutagenic mechanisms of beta-amyrin and stigmasterol